Metabolic reprograming in macrophage polarization. - O'NEILL, LUKE (My University, 2014)
Studying the metabolism of immune cells in recent years has emphasized the tight link existing between the metabolic state and the phenotype of these cells. Macrophages in particular are a good example of this phenomenon. Whether the macrophage obtains its energy through glycolysis or through oxidative metabolism can give rise to different pheno- types. Classically activated or M1 macrophages are key players of the first line of defense against bacterial infections and are known to obtain energy through glycolysis. Alterna- tively activated or M2 macrophages on the other hand are involved in tissue repair and wound healing and use oxidative metabolism to fuel their longer-term functions. Metabolic intermediates, however, are not just a source of energy but can be directly implicated in a particular macrophage phenotype. In M1 macrophages, the Krebs cycle intermediate succinate regulates HIF1 a , which is responsible for driving the sustained production of the pro-inflammatory cytokine IL1 b . In M2 macrophages, the sedoheptulose kinase car- bohydrate kinase-like protein is critical for regulating the pentose phosphate pathway. The potential to target these events and impact on disease is an exciting prospect
PUBLISHED
Keywords: metabolism; macrophage; HIF; glycolysis